Child and adolescent mental health policies and plans - Funk, Michelle; Bhalla, P. (Praveen), 1947-; Saraceno, Benedetto (Mental health policy and service guidance package., 2005)
The module outlines the steps to be followed in the development and implementation of a child and adolescent mental health policy and plan. Its goal is to assist countries to promote the healthy development of children and adolescents.